Forecasting fiscal variables in selected European economies using least absolute deviation method. (11th January 2018) - Žaja, Maja Mihelja; Kržić, Ana Sović; Habek, David
Actual economic crisis initiated numerous debates on fiscal policy of the European Union (EU) and unrealistic convergence demands placed upon the Member States, where the emphasis is on fiscal criteria: The budget deficit should not exceed 3% of Gross Domestic Product (GDP) and the public debt must be less than 60% of GDP. The aim of this article is to analyze the impact of the crisis on fiscal variables in selected European countries and to examine the efficacy of conducted reforms through comparing forecasted values, obtained by the least absolute deviation method, with actual values. Analyzed countries are Portugal, Ireland, Greece, Spain, and the Republic of Croatia, the EU countries that were the most exposed to the impact of the crisis and have problems with economic instability. Values were forecasted on the quarter basis for the period 2015 and 2016 using data from 2000 until 2014, and the results show that the proposed method is useful in predicting under unchanged conditions. This leads to the conclusion that analyzed countries did not carry out all the necessary reforms.